An Amorphous Carbon Nitride Composite Derived from ZIF‐8 as Anode Material for Sodium‐Ion Batteries. Issue 11 (4th May 2015) - Fan, Jing‐Min; Chen, Jia‐Jia; Zhang, Qian; Chen, Bin‐Bin; Zang, Jun; Zheng, Ming‐Sen; Dong, Quan‐Feng
Abstract An composite comprising amorphous carbon nitride (ACN) and zinc oxide is derived from ZIF‐8 by pyrolysis. The composite is a promising anode material for sodium‐ion batteries. The nitrogen content of the ACN composite is as high as 20.4 %, and the bonding state of nitrogen is mostly pyridinic, as determined by X‐ray photoelectron spectroscopy (XPS). The composite exhibits an excellent Na+ storage performance with a reversible capacity of 430 mA h g−1 and 146 mA h g−1 at current densities of 83 mA g−1 and 8.33 A g−1, respectively. A specific capacity of 175 mA h g−1 was maintained after 2000 cycles at 1.67 A g−1, with only 0.016 % capacity degradation per cycle. Moreover, an accelerating rate calorimetry (ARC) test demonstrates the excellent thermal stability of the composite, with a low self heating rate and high onset temperature (210 °C). These results shows its promise as a candidate material for high‐capacity, high‐rate anodes for sodium‐ion batteries.